2019
DOI: 10.1027/1016-9040/a000320
|View full text |Cite
|
Sign up to set email alerts
|

Decision Inertia in Critical Incidents

Abstract: Abstract. When presented with competing options, critical incident decision makers often struggle to commit to a choice (in particular when all options appear to yield negative consequences). Despite being motivated to take action in disasters, terrorism, major investigations, and complex political interventions, decision makers can become inert, looping between phases of situation assessment, option generation, and option evaluation. This “looping” is functionally redundant when it persists until they have lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The extent to which this model is adopted in practice across command levels has yet to be empirically tested. Findings of research conducted in extreme environments show a tendency for individual decision-makers to deviate from linear approaches by avoiding explicit planning (Klein, 1993(Klein, , 2003, or delaying action (Power & Alison, 2018;Waring et al, 2018). However, research is needed that examines processes used to make joint decisions in situ within MTSs operating in extremis to provide a basis for establishing the utility of the JDM for reducing decision inertia and other pitfalls associated with group decisions (Wilkinson, Cohen-Hatton, & Honey, 2019).…”
Section: Practitioner Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which this model is adopted in practice across command levels has yet to be empirically tested. Findings of research conducted in extreme environments show a tendency for individual decision-makers to deviate from linear approaches by avoiding explicit planning (Klein, 1993(Klein, , 2003, or delaying action (Power & Alison, 2018;Waring et al, 2018). However, research is needed that examines processes used to make joint decisions in situ within MTSs operating in extremis to provide a basis for establishing the utility of the JDM for reducing decision inertia and other pitfalls associated with group decisions (Wilkinson, Cohen-Hatton, & Honey, 2019).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…In effect, effort is invested to gathering and assessing information, and considering options, but without progressing to take action. The decision-maker is trapped, continually reevaluating the situation in an attempt to trade-off salient competing goals, options and anticipate potential consequences (Alison et al, 2015;Power & Alison, 2018). Limited understanding of roles and use of agency-specific technical language can also encourage redundant, repetitive deliberation rather than adaptive discussion of action (Waring et al, 2018(Waring et al, , 2019.…”
Section: Decision-making In Extreme Environmentsmentioning
confidence: 99%
“…Thematic analysis of interviews with multi‐agency group members, after they have participated in simulated major incidents, alongside other evidence which suggests that timely action can be constrained by decision inertia (e.g., Power & Alison , ; Alison et al, ; see also Janis, ; Janis & Mann, ). Here, decision inertia refers to “a process of (redundant) deliberation over possible options and in the absence of any further useful information” (Power & Alison, ); which could interact with whether a group is tolerant of uncertainty or not (e.g., Frenkel‐Brunswik, ; see also, van den Heuvel et al, ; for reviews, see Furnham & Marks, ; Hillien, Gutheil, Strout, Smets, & Han, ). Moreover, the separation of “assess risks and develop a working strategy” from “identify options and contingencies” within the JDM might have the unforeseen consequence of limiting rather than encouraging the consideration of alternative options (cf.…”
Section: Naturalistic Decision‐makingmentioning
confidence: 99%
“…Thereby, the process character of a decision is missed, and determinants of decision avoidance are neglected. Decision avoidance is a phenomenon that has been studied in various forms and psychological disciplines [ 1 ]: choice deferral of consumer decisions in marketing research (e.g., [ 2 ]), heuristic and biases of decision avoidance in cognitive psychology (e.g., [ 3 ]), decision inertia in critical incidents in naturalistic decision-making research (e.g., [ 4 ]), procrastination research in educational or business psychology (e.g., [ 5 ]), chronic indecisiveness in clinical psychology or personality psychology (e.g., [ 6 ]). Altogether, there is a bunch of studies in the context of decision avoidance, but they have explored the phenomenon out of the perspective of different and partly unlinked psychological disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in decision situations of high stress, a decision between two unattractive options is often avoided (as studied in status quo bias and omission bias [ 7 , 8 ]). Additionally, research about decisions in the context of critical incidents showed that redundant deliberation about negative consequences results in behavioral inaction and even worse outcomes (decision inertia, [ 4 ]). On the other hand, it seems reasonable to continue searching for new alternatives if time pressure is low, and previous options are unsatisfying [ 2 , 21 ].…”
Section: Introductionmentioning
confidence: 99%